Modul Pembelajaran Sistem Reproduksi Manusia Berbasis Problem Based Learning: Suatu Upaya Penguatan Keterampilan Berpikir Kritis Siswa SMA Kelas XI : (Developing a Problem-Based Learning Module on the Human Reproductive System to Strengthen the Critical Thinking Skills of Grade XI Senior High School Students) - Sianturi , Stephanie Agustin; Silitonga , Melva (BIODIK, 2025)
This study aims to develop, validate, and determine the effectiveness of a Problem-Based Learning (PBL)-based Human Reproductive System Module for Grade XI senior high school students. The research employed the 4D development model, consisting of the define, design, develop, and disseminate stages. The module includes three learning activities: the male reproductive system, the female reproductive system, and disorders of the reproductive system, all designed following the PBL syntax. Validation results indicate a very high level of feasibility from material experts (87.83), learning experts (88.75), design experts (95.31), and biology teachers (91.50). Student responses were also highly positive, with an attractiveness score of 93.33. The effectiveness test showed that learning using this module was effective, with an average individual learning score of 80, a classical completeness of 86%, and an N-gain of 70.51. Therefore, the PBL-based module is feasible and effective in improving students’ learning outcomes and critical thinking skills. Abstrak. Penelitian ini bertujuan mengembangkan dan menguji kelayakan serta efektivitas modul sistem reproduksi manusia berbasis Problem Based Learning (PBL) untuk siswa SMA kelas XI. Penelitian menggunakan model pengembangan 4D yang meliputi tahap define, design, develop, dan disseminate. Modul terdiri atas tiga kegiatan pembelajaran: sistem reproduksi pria, sistem reproduksi wanita, dan gangguan sistem reproduksi, yang disusun mengikuti sintaks PBL. Hasil validasi menunjukkan tingkat kelayakan sangat tinggi dari ahli materi (87,83), ahli pembelajaran (88,75), ahli desain (95,31), dan guru biologi (91,50). Respon siswa juga sangat positif dengan nilai kemenarikan 93,33. Uji efektivitas menunjukkan pembelajaran menggunakan modul ini efektif dengan rata-rata hasil belajar 80, ketuntasan klasikal 86%, dan N-gain 70,51. Dengan demikian, modul berbasis PBL ini layak dan efektif digunakan untuk meningkatkan hasil belajar dan berpikir kritis siswa.